EFEKTIVITAS PEMBELAJARAN TAHSIN JARAK JAUH CINTA QORAN FOUNDATION PADA MASYARAKAT YANG PRODUKTIIF - Ajeng Rahma Nurlita; rizal; Yal Robiansyah (Jurnal Cendekia Ihya, 2024)
This study aims to examine the effectiveness of distance learning (DL) for productive communities in the tahsin Al-Qur'an program organized by the Cinta Quran Foundation. This research focuses on the initial planning, implementation, and impact of the distance tahsin program on participating communities. The research method used is qualitative with a descriptive approach, where data is collected through interviews and observations to understand the phenomena without emphasizing population size. The study results show that the online tahsin learning is effective in improving Al-Qur'an reading skills, with more participants progressing directly to the Al-Qur'an level compared to those starting with the Ummi method. The tahsin program has been conducted online since its inception, can be followed individually or in groups, and targets all ages and professions without geographical limitations. Each tahsin session lasts 20 minutes, with five sessions for regular participants and unlimited sessions for those opting for continuous learning. The program is guided by a curriculum that serves as the learning objective. Supporting factors of this program include free access, flexible timing, and the participants' awareness to be active. Conversely, inhibiting factors include internet network disruptions, limited devices, and scheduling conflicts with participants’ agendas. Regarding its effectiveness, the Cinta Quran Foundation's distance tahsin learning has proven to be effective for busy productive communities, evidenced by 315 participants progressing to the Al-Qur'an level compared to only 21 still studying the Ummi method. In percentage terms, 65% of participants advanced to the Al-Qur'an level after joining tahsin, compared to 35% who were already at this level before joining the program. In conclusion, this program provides positive impacts and serves as an effective alternative for Al-Qur'an learning among productive communities